Lamteuba In Transition: A Socio-Historical Perspective on Agricultural Cultural Change - Asmanidar, Asmanidar (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
This study explores the transformation of agricultural culture in the Lamteuba community from a socio-historical perspective, with particular emphasis on the shift from cannabis cultivation to turmeric farming. The primary objective is to identify the driving factors behind this agricultural transition, the challenges encountered during the process, and the resulting social and cultural impacts. Employing a qualitative approach, data were collected through field observations, in-depth interviews, and documentation. The findings reveal that this shift in agricultural practice was influenced by multiple factors, including adverse experiences stemming from law enforcement actions, rising individual and collective awareness, family influence, government and local authority-led socialization efforts, and the relative ease of cultivating turmeric. The community faced several challenges, such as restoring the village’s reputation, maintaining crop quality, coping with unpredictable environmental conditions, and acquiring knowledge on turmeric cultivation. The transition has had a positive impact, marked by improved social stability, enhanced household economic sustainability, and renewed hope for a future free from the negative stigma that once plagued the village. Thus, this agricultural shift reflects not only a change in commodity production but also a broader transformation in the identity and social structure of the Lamteuba community